Pembelajaran Matematika pada Materi Perkalian di Sekolah Dasar dengan Berbantuan Alat Peraga - Nurwahida; Irajuana Haidar (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2023)
The implementation of this study aims to determine the appropriate teaching aids for multiplication material in elementary schools. The design of this research is library research by preparing equipment, compiling a work bibliography, managing time, reading and making research notes. The props used to teach multiplication material are KOBELA (Magic Learning Box), Jarimatika and Multiplication Board. with the results of the literature review, it can be concluded that teaching aids function to explain or demonstrate a subject in the teaching and learning process on multiplication material.